Topical Adipose Mesenchymal Stem cell metabolites regulate the expression of MMP-1, MMP-9, EGF, TGF-β in oral mucosa ulcer rat model - Hendri Susanto; Ade Ratu Mas Saraswati; Alexander Patera Nugraha; Satutya Wicaksono; Nanan Nur'aeny; Diah Savitri Ernawati (Elsevier, 2024)
Objective: Matrix metalloproteinase (MMP-1 and −9), Epidermal Growth Factor (EGF), and Transforming Growth factor (TGF)-β are expressed in the oral ulcer wound-healing process. The Adipose mesenchymal stem cell metabolites (AdMSCMs) may accelerate wound-healing. This study aimed to investigate the expression of MMP-1, MMP-9, EGF, and TGF-β in the oral mucosa ulcer rat model treated with topical AdMSCMs. Materials and Methods: Oral ulcer models were created in twenty healthy male Wistar rats (Rattus novergicus) divided into AdMSCMs and control groups. The oral ulcer model was treated topically using AdMSCMs oral gel three times daily for 3 and 7 days. The expression of MMP-1, MMP-9, EGF, TGF-β was evaluated through histological examination using the immunohistochemistry method. Independent t-test was used to compare the mean of expression of MMP-1, MMP-9, EGF, TGF-β between control and treatment groups (AdMSCMs), and paired t-test was used to analyze the mean between day 3 and day 7 of each group. Results: A lower expression of MMP-1, MMP-9 in AdMSCMs group and higher expression EGF and TGF-β in AdMSCMs group compared to the control group in day 3 and day 7. Independent t-test results showed a significant difference in the expression of MMP-1, MMP-9, EGF between the control and AdMSCMs group in day 3 and day 7. Only TGF-β expression mean difference between day 3 and day 7 showed a significant difference compared to the control groups (p < 0.05) Conclusions: AdMSCMs oral gel may accelerate oral ulcer healing models by reducing the expression MMP-1, MMP-9, and increasing EGF and TGF-β expressions during the wound-healing process.